A Fixed Point Technique for Solving an Integro-Differential Equation Using Mixed-Monotone Mappings - Hasanen A. Hammad; Rashwan A. Rashwan; Manuel De la Sen (Journal of Function Spaces)
The objective of this manuscript is to present new tripled fixed point results for mixed-monotone mappings by a pivotal lemma in the setting of partially ordered complete metric spaces. Our outcomes sum up, enrich, and generalize several results in the current writing. Moreover, some examples have been discussed to strengthen and support our theoretical results. Finally, the theoretical results are applied to study the existence and uniqueness of the solution to an integro-differential equation.